2012
DOI: 10.1177/1744987112458670
|View full text |Cite
|
Sign up to set email alerts
|

The cross-contamination potential of mobile telephones

Abstract: The use of mobile devices for professional, business, educational, personal and social purposes has accelerated exponentially over the last decade. Staff working in health care organisations, and patients and visitors using healthcare settings, understandably want to use mobile technology.Concerns have been raised about safety in terms of interference with equipment, threats to privacy and dignity, yet less policy attention has been paid to infection risks.Healthcare professional students were supplied with sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…However, TMPs/Ds had significantly higher microbial load than KMPs. Several studies have reported high contamination levels similar to those found in this study [2,[5][6][7]16].…”
Section: Discussionsupporting
confidence: 85%
“…However, TMPs/Ds had significantly higher microbial load than KMPs. Several studies have reported high contamination levels similar to those found in this study [2,[5][6][7]16].…”
Section: Discussionsupporting
confidence: 85%
“…One study on cross-contamination [41] showed that MPs contained significant amounts of pathogenic microorganisms, but that the bacterial contamination could easily be terminated by cleaning. Zhao et al (2008) [54], by [56], and others [31,55,42] showed that the contaminations of the MPs used by medical employees can be effectively reduced by hand washing with water or alcohol and that MPs can be disinfected by the use of 70% ethyl or isopropyl alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…A bacterial suspension of 1·0–1·5 × 10 8 CFU ml −1 was prepared in maximum recovery diluent (MRD; Lab M) as per previous methods (BSI ; White et al . ). From this bacterial stock, a 1·0–1·5 × 10 5 CFU ml −1 suspension was prepared in SWF (50% v/v foetal calf serum (Sigma‐Aldrich Ltd, Gillingham, UK) in MRD) and used as an inoculum for subsequent testing.…”
Section: Methodsmentioning
confidence: 97%